Fabrication of 3D-Printed Flow Cell Biosensor for Pathogenic Escherichia Coli Bacteria Detection - Muhammad Fadzlisyam Redzuan; Irfan Danial Ismadi; Muhammad Fakhrullah Mohamad Azmi; Izzah Afifah Ibrahim; Mohd Ifwat Mohd Ghazali; Nurul Azmawati Mohamed @ Abd Aziz; Nizam Tamchek; Shahino Mah Abdullah (Kolej PERMATA Insan, 2025)
International Conference And Innovation On Education, Science & Technology (ICIEST 2025) “Fostering Innovation And Creativity Through Education, Science & Technology” 21st June 2025 Editor : Hatika Kaco, Diani Mardiana Mat Zin, Fadzidah Mohd Idris, Siti Munirah Mohd Nurhidaya Mohamad Jan, Nor Atirah Izzah Zulkefli, Nadiah Suboh Organised by : Education & Advanced Sustainability (EdAS) unit, Kolej PERMATA Insan, Universiti Sains Islam Malaysia